Improving Critical Thinking using a Guided Inquiry Approach assisted by PhET Simulations in Wave Material - Marina, Dewi; Marwanti, Kissi; Astra, I Made (Jurnal Penelitian Pembelajaran Fisika, 2024)
This research shows that using guided inquiry with PhET simulations significantly improves students' critical thinking skills. In this study, Classroom Action Research (Penelitian Tndakan Kelas) method was used with the participation of 39 students of Class XI IPA 3 SMAN 6 Tangerang Regency. Data collection spanned three learning cycles comprising planning, action implementation, observation, and reflection. outcomes consistently showed progress across cycles, with the average score on critical thinking tests rising from 65 pre-intervention to 80 by the third cycle. Moreover, the percentage of students achieving a "Very Good" rating increased significantly from 10% to 20% in cycle III. Observations highlighted heightened student engagement and underscored the pivotal roles of teacher and peer feedback in advancing critical thinking skills. Consequently, the guided inquiry method complemented by PhET simulations effectively cultivated a vibrant and efficacious learning atmosphere that fostered students' critical thinking capabilities.